APPLICATION OF THE PRINCIPLE OF JUSTICE IN AN EFFORT TO PROVIDE LEGAL PROTECTION TO INSURANCE POLICY HOLDERS - harvia santri, selvi; Novrista Syahfitri, Naia; Ismael, Taufik (International Conference On Law And Social Sciences, 2024)
The agreement that occurs between the insurer and the insured in insurance is stated in a written deed called a policy. Issuance of policies in insurance has been prepared in advance by the insurance company. This can bring a sense of injustice to the parties, namely the insured, who feels their position is weak because they do not participate in determining the contents of the agreement, resulting in an interpretation that the insurance company tends to protect its interests in such a way by stipulating a number of provisions that limit the rights of the insured so that the contract The standard has the potential to become a one-sided clause. Therefore we need a form of legal protection for the insured